Строительство атомных электростанций: [учебное пособие] - Дубровский В. Б. Виталий Борисович; Лавданский П. А. Павел Александрович; Нешумов Ф. С. Феликс Сергеевич; Пономарев Ю. В. Юрий Васильевич; Кириллов А. П. Александр Петрович; Конвиз В. С.; Кузнецов А. (Москва, Мир, 1981)
На английском языке